1988
DOI: 10.1111/j.1365-2257.1988.tb00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Venous and Skin puncture blood counts compared

Abstract: Venous and skin puncture blood counts were compared in 80 paired samples from 33 children, aged 6 months to 14 years, and 10 adults. Significantly higher mean values for Hb, RBC, haematocrit and neutrophils were found in skin puncture blood in children whereas platelet values were slightly higher in venous blood. Similar results were found in adult samples. Only occasionally were differences likely to be of clinical importance. The excellent comparability of paired platelet counts, at variance to that found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…A number of factors may contribute to the differences between the findings of the present and earlier reports, including the number and race of the children studied, the methods employed, and the type of sample used. For example, Cranendonk et al (1985) used capillary blood which gives leucocyte values some 3–12% higher than those found in paired venous samples ( Bellamy & Hinchliffe 1988; Cracknell, Hinchliffe & Lilleyman 1995). This may contribute to, but cannot entirely explain, the differences in the lower limits of the leucocyte and neutrophil values between the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors may contribute to the differences between the findings of the present and earlier reports, including the number and race of the children studied, the methods employed, and the type of sample used. For example, Cranendonk et al (1985) used capillary blood which gives leucocyte values some 3–12% higher than those found in paired venous samples ( Bellamy & Hinchliffe 1988; Cracknell, Hinchliffe & Lilleyman 1995). This may contribute to, but cannot entirely explain, the differences in the lower limits of the leucocyte and neutrophil values between the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the capillary WBC is higher than the venous WBC in adults [35], children [36,37] and neonates [38]. In addition, the venous blood was diluted with anticoagulant, which could also account for the lower number of leukocytes in venous blood Table 4 The Spearman correlation coefficient between aggregation parameters in capillary and venous blood and the acute phase reactants.…”
Section: Discussionmentioning
confidence: 99%
“…The largest discrepancies in Hb concentrations between venous and capillary were reported in the neonatal period and specifically in acutely ill children, with the Hemocue producing lower values than the laboratory analysers. The highest difference between the two sample types was seen in anaemic children [8,9,16,18,19].…”
Section: Venous Versus Capillary Blood Samplesmentioning
confidence: 91%